2015
DOI: 10.4269/ajtmh.14-0499
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-Acquired Dengue Virus Infections Do Not Reduce Short-Term Survival of Infected Aedes aegypti from Ho Chi Minh City, Vietnam

Abstract: Transmission of dengue virus (DENV) from mosquito to human is dependent upon the survival of the mosquito beyond the virus extrinsic incubation period. Previous studies report conflicting results of the effects of DENV on Aedes aegypti survival. Here, we describe the effect of DENV on the short-term survival (up to 12 d) of 4,321 Ae. aegypti mosquitoes blood-fed on 150 NS1-positive dengue patients hospitalized in the Hospital for Tropical Diseases, Ho Chi Minh City, Vietnam. Mosquito survival was not different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…), consistent with the wide distribution of its main vector Aedes aegypti [912]. All the administrative levels report either autochthonous cases (>90% of the territories) or imported cases (as occurs in Bogota, the capital city).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…), consistent with the wide distribution of its main vector Aedes aegypti [912]. All the administrative levels report either autochthonous cases (>90% of the territories) or imported cases (as occurs in Bogota, the capital city).…”
Section: Introductionsupporting
confidence: 61%
“…No research has been conducted to assess the various factors which drive dengue transmission in this setting [20]. Those factors include education, economic income [21], migration and population flows [22], cross-protection between serotypes [12, 23], and the environmental factors which have influenced dengue epidemiology, including climate change [24, 25], and housing standards [2628]. All of these are important in order to develop effective integrated interventions oriented to reduce transmission and the burden of disease in a given area.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies report no effect of DENV on fitness in A. aegypti (Carrington et al. ) others have measured reductions in survival and fecundity (Maciel‐de‐Freitas et al. ) and feeding and oviposition success (Sylvestre et al.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies report no effect of DENV on fitness in A. aegypti (Carrington et al 2015) others have measured reductions in survival and fecundity (Maciel-de-Freitas et al 2011) and feeding and oviposition success (Sylvestre et al 2013). Such discrepancies are likely explained by differences in how fitness is measured and the virus × mosquito genotype combinations tested.…”
Section: Trade-offsmentioning
confidence: 99%
“…Carrington et al . () reported that Ae. aegypti that acquired a dengue infection by feeding on hospitalized dengue patients, the most natural route of infection, did not show a difference in survival compared to mosquitoes that were not infected for a period of 12 days post‐feeding.…”
Section: Discussionmentioning
confidence: 99%